The Effect of Drying Time of Pearl Shells (Pinctada penguin) on Nutrition and Mineral Quality in the Strait of Buton - Asis Surajat; Anita Mustika Ibrahim (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
Pearl shells were one of the mineral sources for ruminant and non-ruminant animal feed. Several studies on pearl shells present results of different nutritional and mineral content caused by several factors, including the geographical location of an area and the processing process. The purpose of this study was to determine the effect of different drying times on the quality of the Nutrient and Mineral content of the Pinctada penguin shells in the Buton Strait. The research design used was a completely randomized design with four treatments and four replications, each replication consisting of 400 grams of Pinctada penguin. The research sample was dried at 1200C for 15, 30, and 45 minutes for each treatment. Then an analysis was carried out to see the levels of calcium (Ca), Iron (Fe), Zinc (Zn), Protein, Fat, Phosphorus (P), Potassium (K), and Iodine (I). The research data were analyzed using analysis of variance (ANOVA) based on RAL using the SPSS standard. If the treatment has a significant effect, further tests are carried out with the Duncan Multiple Range Test.